2017
DOI: 10.1002/14651858.cd012600
|View full text |Cite
|
Sign up to set email alerts
|

First trimester ultrasound tests alone or in combination with first trimester serum tests for Down's syndrome screening

Abstract: Test strategies that combine ultrasound markers with serum markers, especially PAPP-A and free ßhCG, and maternal age were significantly better than those involving only ultrasound markers (with or without maternal age) except nasal bone. They detect about nine out of 10 Down's affected pregnancies for a fixed 5% FPR. Although the absence of nasal bone appeared to have a high diagnostic accuracy, only five out of 10 affected Down's pregnancies were detected at a 1% FPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 671 publications
3
72
0
11
Order By: Relevance
“…In the United Kingdom, color Doppler and pulsed-wave Doppler are not routinely employed as a part of first-trimester screening for trisomies [17]. Nevertheless, some operators are familiar with such advanced sonographic screening strategies [18] and may, therefore, choose to use Doppler and pulsed-wave Doppler as part of first-trimester screening [19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…In the United Kingdom, color Doppler and pulsed-wave Doppler are not routinely employed as a part of first-trimester screening for trisomies [17]. Nevertheless, some operators are familiar with such advanced sonographic screening strategies [18] and may, therefore, choose to use Doppler and pulsed-wave Doppler as part of first-trimester screening [19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of first-trimester DS screening tests has been demonstrated in large prospective international studies, with a combined test showing over 90% detection of T21, and a false-positive rate of 3-5% [9][10][11][12]. Additionally, several prospective and retrospective multicentric studies have shown the accuracy of advanced first-trimester screening using different software programs, and different test strategies.…”
Section: Introductionmentioning
confidence: 99%
“…1 Today a detection rate of 90% from Down syndrome for a 3% to 5% false-positive rate is expected. [2][3][4] FTS maternal serum markers are detected through automated laboratory techniques and have well-established quality controls.…”
Section: Introductionmentioning
confidence: 99%